THE NON-DOGMATIC IMAGE OF COMPARATIVE LAW - Citrawan, Harison (Mimbar Hukum, 2024)
Abstract This study discusses the epistemological dimension of critiques of comparative law. It contends that the critiques rest upon what I call mode of differentiation, an epistemology of comparing ‘the other than’ or ‘the different from’. The argument builds upon reexamining some contemporary critical approaches to comparative law from a Deleuzian jurisprudence, a jurisprudential reflection of law as singularity and constant becoming. Particularly, this study makes the case of four modes of differentiation, i.e., distancing, perception, otherness, and movement. These modes of differentiation can be seen as comparativist-at-law’s endeavor to differentiate conscious ideas at work and to attend to the concept-creation of law and lawful relations in foreign legal systems. Accordingly, the image of comparative law must be based on three main features: (1) it seeks perceptual rather than conceptual understanding of law; (2) it is non-dogmatic in a sense that it breaks free from the transcendence in comparison, thus mapping the becoming of legal assemblages; and (3) it abandons hierarchization to the extent that comparison is directed at the openness to problematize, experiment and create. This epistemological move can largely be supportive of the interpretive account of comparative law, seen to be one of the fundamentals in advocating the critical dimension of comparative law. Abstrak Penelitian ini membahas dimensi epistemologis dari kritik terhadap perbandingan hukum. Penelitian ini berpendapat bahwa kritik-kritik tersebut bertumpu pada apa yang saya sebut sebagai modus diferensiasi, yaitu sebuah epistemologi yang membandingkan 'yang lain dari' atau 'yang berbeda dari'. Argumen ini dibangun dengan memeriksa kembali beberapa pendekatan kritis kontemporer terhadap hukum perbandingan dari yurisprudensi Deleuzian, sebuah refleksi yurisprudensial tentang hukum sebagai keunikan dan menjadi konstan. Secara khusus, penelitian ini membahas empat modus diferensiasi, yaitu jarak, persepsi, keanehan, dan pergerakan. Modus-modus diferensiasi ini dapat dilihat sebagai upaya para ahli perbandingan hukum untuk membedakan ide-ide yang disadari di tempat kerja dan untuk memperhatikan penciptaan konsep hukum dan hubungan-hubungan hukum dalam sistem-sistem hukum asing. Oleh karena itu, citra perbandingan hukum harus didasarkan pada tiga fitur utama: (1) mencari pemahaman perseptual daripada pemahaman konseptual tentang hukum; (2) tidak dogmatis dalam arti membebaskan diri dari transendensi dalam perbandingan, dengan demikian memetakan pembentukan kumpulan hukum; dan (3) meninggalkan hirarki sejauh perbandingan diarahkan pada keterbukaan untuk mempermasalahkan, bereksperimen, dan berkreasi. Langkah epistemologis ini sebagian besar dapat mendukung penjelasan interpretatif tentang perbandingan hukum, yang dipandang sebagai salah satu dasar dalam mengadvokasi dimensi kritis dari perbandingan hukum.